K výzvám společnosti vědění adresovaným škole. / The role of school in the knowledge society and the consequences of social changes for school. - Petra Valentová (Czech Pedagogical Society, 2013)
Knowledge society - a term denoting many theoretical approaches tounderstanding today's presence which has also become a part of many public documents. The goal of the article is to examine and summarize characteristic features exhibited by our presence which entitle this term to be used; it also brings the opinions of social critics - the critics of the knowledge society concept. It alsocontemplates the newly defined role of the man in the world of work and the consequences and new targets that follow from the knowledge society concept for school. At the same time, it indicates the responsibility of the society to school for the school is a central institution in the knowledge society but it does not always enjoy the adequate respect.